G568(P) Standardisation of paediatric handovers- a quality improvement project. (27th April 2016) - Wilegoda, MSS; Gupta, C; Khattak, J; Aidoo-Micah, G; Chowdhury, L
Abstract : Context: Structured communication, especially at the time of handovers is essential to promote patient safety. Mnemonics are memory aids hence can be used as an effective communication tools. SBAR mnemonic is effectively used as a situational briefing tool and is appropriate for use across hierarchical boundaries and emergency situations. But, there are limitations in its applicability in routine handovers, particularly in situations that include transmission of information about complex patients who require broader information and context. IPASS which is an evidence-based, standardised approach to teaching, evaluating, and improving handovers is widely being used in North America and is being introduced in UK. IPASS stands for Illness Severity, Patient Summary, Action List, Situation Awareness and Contingency Planning and Synthesis by Receiver. Problem: With the implementation of European Working Time Directive in UK, the number of medical handovers has increased significantly there by increasing the potential for communication gaps which can further compromise patient safety. Most medical schools in UK do not have curriculum based handover teaching and our survey from foundation doctors did reflect this. Also, as people vary in the way they communicate due to cultural, intellectual and social factors, standardisation of the handovers becomes more important to eliminate the risks posed by different communication styles. Assessment of problem and analysis of its causes: We aimed to standardise patient handovers by introducing IPASS. Initial assessment of the handovers was done using standardised observation of the handovers by using a pre-tested questionnaire proforma and by collecting responses on survey monkey from doctors of all tiers. These assessments highlighted the need to standardise the handovers. Intervention: IPASS was then introduced. Study design: The handovers were prospectively monitored for the implementation of IPASS. Strategy for change: Small workshops, power point presentations, wall charts and pocket cards were used to teach IPASS. The format of the handover sheet was changed as per IPASS. Staff members received continuous support and guidance during the implementation process. Handovers were monitored and feedback was provided regularly. Measurement of improvement: After 6 months, handovers were re-evaluated with the same assessment tools that were used pre- IPASS. Effects of changes: With IPASS, the use of standard communication for handovers was increased by 17%, identification of the sickest patients increased by 23% and provision of action plan for all patients was improved by 24%. The contingency plan was made during handovers for most of the sick patients and overall, there was improvement of 10% regarding contingency plans for all the patients. Gaining the situational awareness became sort of a practice in the unit. Out of all respondents, 74% thought that IPASS overall improved the handovers. Lessons learnt: IPASS improved the handovers by standardising the communication. It is now being introduced into the Trust induction for all the doctors. An e-learning module is also being prepared for the benefit of final year medical students from Birmingham University. Message for others: IPASS is a good communication tool to standardise handovers there by to promote patient safety.